Non-formal Science Education: Moving Towards More Inclusive Pedagogies for Diverse Classrooms - Genco Guralp; Martin McHugh; Sarah Hayes (Center for Educational Policy Studies Journal)
The Diversity in Science towards Social Inclusion–Non-formal Education in Science for Students’ Diversity (DiSSI) project aimed to provide a holistic perspective on diversity, focusing specifically on cultural and ethnic identities, language, socioeconomic background, gender, as well as differing levels of achievement. In particular, the work presented in this paper aims to tackle consciously the issues surrounding teaching and learning in socio-economically deprived areas through non-formal education. This paper presents the results of a pilot study that examined how students participating in non-formal education engage with multi-modal pedagogical approaches designed to address multiple dimensions of diversity via an intersectionality lens. Working with diverse groups requires varied methods; as such, a mixed-method approach was employed in the study to ensure the research team authentically captured and engaged with the lived experiences of the participants. The study aimed to generate best practices that augment the science capital of students, which are applicable across various contexts of diversity. The pedagogical approaches, while not novel in science education literature, were rarely utilised by the teacher and thus were rarely experienced by the students. Participants reported a greater sense of autonomy and ownership of the science through participation in the DiSSI programme. Preliminary results indicate an overall positive experience for students and teachers alike and offer insights into the overall lived experiences of participants, which inform future work.